2022
DOI: 10.1158/1538-7445.sabcs21-p3-17-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P3-17-05: Physicians’ attitudes and perceived barriers to adherence to national breast cancer clinical practice guidelines (BCCPG) in Mexico

Abstract: Background: Adherence to BCCPG improves clinical outcomes for patients with breast cancer. However, implementation of international BCCPG may not be feasible in low- and middle-income countries (LMICs) due to limitations in resources and personnel. A potential solution for this issue is developing national/regional guidelines considering local healthcare contexts. In Mexico, the National Consensus on Diagnosis and Treatment of Breast Cancer (known as the Colima Consensus, http://consensocancermamario.com) is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the past, many of these guidelines have been published in the Mexican Journal of Oncology, with some being in the list of the most downloaded manuscripts of our journal 2 . We recently evaluated the adherence to one of those guidelines, the Consenso Mexicano sobre Diagnóstico y Tratamiento del Cáncer Mamario (Mexican Consensus on Diagnosis and Treatment of Breast Cancer) among members of SMeO, with initial results presented at the 2021 San Antonio Breast Cancer Symposium 3 . Interestingly, we found that a large proportion of cancer care providers adhered to the recommendations of the Consensus, and that a significant number, particularly those working at public institutions, used it as their main clinical practice guideline for the treatment of breast cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, many of these guidelines have been published in the Mexican Journal of Oncology, with some being in the list of the most downloaded manuscripts of our journal 2 . We recently evaluated the adherence to one of those guidelines, the Consenso Mexicano sobre Diagnóstico y Tratamiento del Cáncer Mamario (Mexican Consensus on Diagnosis and Treatment of Breast Cancer) among members of SMeO, with initial results presented at the 2021 San Antonio Breast Cancer Symposium 3 . Interestingly, we found that a large proportion of cancer care providers adhered to the recommendations of the Consensus, and that a significant number, particularly those working at public institutions, used it as their main clinical practice guideline for the treatment of breast cancer.…”
mentioning
confidence: 99%
“…Interestingly, we found that a large proportion of cancer care providers adhered to the recommendations of the Consensus, and that a significant number, particularly those working at public institutions, used it as their main clinical practice guideline for the treatment of breast cancer. Interestingly, the main obstacles for its implementation included logistical barriers and the lack of multidisciplinary teams and resources 3 . These results highlight the relevance of creating and publishing 2565-005X/© 2022 Sociedad Mexicana de Oncología.…”
mentioning
confidence: 99%